Answer: The answer is 6.
The number sentence is
3-3=0
10-4=6
So, 13-7=6
Step-by-step explanation:
To solve
, by making ten
First break 13 and write ![13=10+3](https://tex.z-dn.net/?f=13%3D10%2B3)
Then break 7 as ![7=3+4](https://tex.z-dn.net/?f=7%3D3%2B4)
Now to subtract 7 from 13,
Step 1. Subtract 3 (a part of 7), from 3(a part of 13) or cross 3 circles, then we have left 10-4
![13-7=10+3-(3+4)=10+3-3-4=10-4](https://tex.z-dn.net/?f=13-7%3D10%2B3-%283%2B4%29%3D10%2B3-3-4%3D10-4)
Step 2. Subtract 4 from 10 or cross 4 circles out of 10, we get 6.
The answer is 6.
Answer:
The answer is 170
Step-by-step explanation:
Because 8 + 9 = 17, if we multiply all of these values by ten or add a zero to the end of each number, we should get
80 + 90 = 170
Answer:
Step-by-step explanation:
<u>Solving in steps:</u>
<u>1. If 3x - 7 > 0</u>
<u>2. If 3x - 7 < 0</u>
Answer y=-4
Because it's like you do if backwards